Persistence of tree relicts in the Spanish Central System through the Holocene - Abel Schaad, Daniel; Pulido, Fernando; López Sáez, José Antonio; Alba Sánchez, Francisca; Nieto Lugilde, Diego; Franco Múgica, Fátima; Pérez Díaz, Sebastián; Ruiz Zapata, M. Blanca; Gil García, M. José; Dorado Valiño, Miriam (Lazaroa, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false <![endif]–> Persistence of relict tree species in Mediterranean environments is becoming increasingly unlikely in view of ongoing and future global change. The variability in the Holocene climate and more recent anthropogenic impacts have driven many populations to fragmentation and isolation, and even to extinction. However, some have persisted to the present day. The understanding of their evolution requires long-term studies, in which pollen analysis is a key approach both for formulating hypotheses and supporting results from other disciplines. Mountain ranges have played and still play an essential role as both glacial and interglacial refugia during the Quaternary. The Spanish Central System harbors an exceptional diversity due to its geographical location and complex topography. Some cold-adapted species have survived here with significant proportions of their southernmost populations, often displaying striking adaptations to their changing environments. This work contains a comprehensive review of the palynological investigations conducted in the Spanish Central System, and reveals the distribution of genera such as Taxus, Betula, Fagus, Carpinus and Tilia throughout the Holocene. We also highlight the scarcity of well-dated and high-resolution works, which may contribute to a better understanding of their recent and future evolution. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin:0pt; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –>